Laterality and Usability: Biomechanical aspects in prehension strength - Paschoarelli, Luis Carlos [UNESP]; Razza, Bruno Montanari [UNESP]; Lúcio, Cristina do Carmo [UNESP]; Ulson, José Alfredo Covolan [UNESP]; Silva, Danilo Corrêa [UNESP] (My University, 2012)
Although technological developments in recent decades have improved the quality of life for many, a number of user interface problems still exist. There are difficulties, for example, manipulating manual instruments by those with specific needs, especially left-handed users. The design of such instruments depends on scientific knowledge of biomechanical forces - especially prehension. The aim of this study was to analyze biomechanical effort during simulated manual activities (compression, traction and torque with 14 different manual interfaces) between dominant and non-dominant hands. Sixty individuals (30 left-handed) participated in the study. Measurements were taken with an advanced force gauge and a static torque transducer. The results indicate that right-handed individuals perform better (p = 0.05) with the dominant hand (in 12 manuals interfaces), while there were no significant strength differences among the left-handed (except for two manual interfaces). The reasons why left-handed individuals present little difference in strength between the dominant and non-dominant hands are not clear, but could be the result of frequent use of the non-dominant hand to perform many instrumental activities of daily living (IADLs). Moreover, it could be due to greater symmetry in the organization of brain hemispheres compared to the strong lateralization of righthanded individuals. The results provide insight into the dynamics of the manipulation of a number of manual instruments according to right and left-handed groups.
Keywords: Biomechanics; Ergonomic design; Laterality